Understanding the Essence of the Prophet Muhammad’s Prayer in the Perspective of the Qur’an: A Study of Thematic Interpretation - Didik Hariyanto; Sohib Syayfi; Muklasin (Technium Social Sciences Journal, 2024)
This study aims to explore the essence of the prayer of the Prophet Muhammad sallallahu’alaihi wa sallam in the Qur’an by analyzing various interpretations from scholars of related verses. This research is a qualitative study that uses a library research approach, also known as literature review. The thematic interpretation method (Maudu’i) with the Science of interpretation approach is used as a foundation for analyzing. Data were collected through direct recitation and study of Qur’anic verses as well as secondary literature relevant to the research topic. Data analysis is carried out descriptively to provide a clear picture of the object of research based on the collected data. The findings of this study show that the Prophet Muhammad’s prayers in the Qur’an reflect a sincere form of worship to Allah as well as an expression of his total obedience to all His commandments, both to ask for His protection and to seek His pleasure. The Prophet’s prayer begins with praise to God, is done without despair, with patience and firm hope, and is based on a deep sense of devotion to Him. His purpose was to be a noble servant before God.